Heterogeneous Photocatalytic Decolourization of Cobalamine in the Presence of Aqueous Titanium Dioxide Suspensions - F. Halbus, Ahmed; H. Hussein, Falah (Asian Journal of Chemistry, 2012)
The objective of this research was to investigate experimentally the decolourization of cobalamine (a-(5,6-dimethylbenzimidazolyl) cobamidcyanide with a chemical formula (C63H88N14O14CoP) under different conditions. The photocatalytic decolourization of cobalamine was carried out in aqueous solution of titanium dioxide (TiO2 Degussa P25) using UVA source of irradiation. The results showed that a complete decolourization was achieved in less than 30 min, however the percent of mineralization was only 80 % after 7 h of irradiation under same conditions. It was noticed that pH of reactants was changed at the end of reaction towards 7 independent on the initial pH. The effect of various parameters, such as photocatalyst amount, cobalamine concentration, addition of H2O2 and flow rate of O2 on photocatalytic oxidation were investigated. The results indicated that the photocatalytic decolourization of cobalamine was well described by pseudo first order kinetics according to the Langmuir-Hinshelwood model. The effect of temperature on the efficiency of photodecolourization of cobalamine was also studied in the range 278-298 K. The activation energy was found to be equal to 22 ± 1 kJ mol-1.